2013
DOI: 10.1089/hgtb.2012.195
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Modifications in Adeno-Associated Virus Serotype 8 Capsid Improves Its Hepatic Gene Transfer Efficiency In Vivo

Abstract: Recombinant adeno-associated virus vectors based on serotype 8 (AAV8) have shown significant promise for liver-directed gene therapy. However, to overcome the vector dose dependent immunotoxicity seen with AAV8 vectors, it is important to develop better AAV8 vectors that provide enhanced gene expression at significantly low vector doses. Since it is known that AAV vectors during intracellular trafficking are targeted for destruction in the cytoplasm by the host-cellular kinase/ubiquitination/proteasomal machin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 59 publications
1
55
2
Order By: Relevance
“…A previous study indicated that the K137R-mutated AAV8 vector resulted in a 10-fold increase of hepatic gene transfer compared with the wild-type AAV8 (Sen et al, 2013b); however, our current data showed only moderate increase of hepatic gene transfer. These conflicted results prompted us to repeat the similar experiments in a different lab using a different reporter gene.…”
Section: Aav8-k137r Mutant With Luciferase Reportercontrasting
confidence: 91%
See 4 more Smart Citations
“…A previous study indicated that the K137R-mutated AAV8 vector resulted in a 10-fold increase of hepatic gene transfer compared with the wild-type AAV8 (Sen et al, 2013b); however, our current data showed only moderate increase of hepatic gene transfer. These conflicted results prompted us to repeat the similar experiments in a different lab using a different reporter gene.…”
Section: Aav8-k137r Mutant With Luciferase Reportercontrasting
confidence: 91%
“…Indeed, delivering the mutated AAV2 vector in vivo by tail vein injection resulted in higher vector copy numbers (up to 4.9-fold) and transgene expression in hepatocytes (up to 14-fold) (Gabriel et al, 2013). This strategy was also applied to the other serotypes by the same group such as AAV1, AAV5 (Sen et al, 2013a), and AAV8 (Sen et al, 2013b), and similar increases of gene transduction efficiency (up to 16-fold) were observed. In particular, the single-amino acid 137 K-R mutation on AAV1 (AAV1-K137R) and AAV8 (AAV8-K137R) resulted in consistently higher hepatocyte transgene expression in vivo with a 5-10-fold increase compared with the original capsids (Sen et al, 2013a,b).…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations